Tubulin isotypes: generation of diversity in cells and microtubular organelles. - Gull, K; Hussey, P; Sasse, R; Schneider, A; Seebeck, T; Sherwin, T (1986)
Diversity of tubulin isotypes is illustrated by consideration of the beta-tubulin isotypes of higher plants and the eukaryotic microbe, Physarum polycephalum, and by the alpha-tubulin isotypes of the protozoan, Trypanosoma brucei. The carrot plant expresses six, well-defined beta-tubulin isotypes that possess characteristic two-dimensional gel coordinates. These six beta-tubulin isotypes are differentially expressed during development of the flowering plant. In a similar manner, Physarum expresses three separate beta-tubuli isotypes during its life cycle; of the two beta 1 isotypes, one is expressed solely in the myxamoeba whilst the other is expressed both in the myxamoeba and in the plasmodium. A further beta-tubulin isotype, beta 2, is expressed only in the plasmodium. In carrot and in Physarum the generation of beta-tubulin diversity appears, in the main, to be generated by the differential expression of a beta-tubulin multi-gene family. However, tubulin isotypes can also be generated by post-translational modifications and T. brucei utilizes two different modifications within one cell. First, the primary translation product, the alpha 1-tubulin isotype, can be acetylated to produce the alpha 3 isotype. Second, both the alpha 1 and alpha 3 isotypes appear to exist in both tyrosinated and detyrosinated forms. The generation of these alpha-tubulin isotypes within the same cell and their presence in particular cellular domains, modulated throughout the cell cycle, reveals a complex relationship between alpha-tubulin isotypes produced by post-translational modifications and the dynamics of microtubule construction.